Designing Assessment in Elt Courses Based on Team-Based Project - Satria, Benni; Nainggolan, Elsa Ernawati; Hanifah, Hanifah; Candra, Muhammad; Agust, Satria (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
In order to stay current in the learning process, every course had to be frequently redesigned. Presently In Indonesia, there were two learning models emphasized namely team-based project and case-method. In this paper, we aimed at designing a syllabus for teaching assessment in ELT oriented on team-based project developed in Universitas Maritim Raja Ali Haji. Team-based project was designed to involve and encourage all students in the class to be active in the process of teaching and learning. The syllabus focused on a class project for the final activity. The project must be based on the current issues and topics addressing the meaningful learning. It was expected that the project can help the students of the department to prepare them for their future career as English language teachers. This study used a Research and Development (R&D) method involving analyzing, designing, developing, implementing, and evaluating. The data were collected by utilizing interview, expert judgment, observation, and test. The subject of this study was a class of ELT students. The study showed the procedure for designing Assessment in ELT Courses based on team-based project. The findings also showed the validity, practicality, and effectiveness of the syllabus.